The authors reply: Letter on: "Pitfalls in the measurement of muscle mass: a need for a reference standard" by Clark et al. Issue 7 (29th January 2019) - Buckinx, Fanny; Landi, Francesco; Cesari, Matteo; Fieding, Roger A.; Visser, Marjolein; Engelke, Klaus; Maggi, Stefania; Dennison, Elaine; Al‐Daghri, Nasser M.; Allepaerts, Sophie; Bauer, Jurgen; Bautmans, Ivan; et al.
Abstract: However, semantics aside, we think that DXA can indeed serve as a reference standard for measuring muscle mass. Obviously, CT and MRI are advanced techniques that can and have been used to obtain important information such as muscle size/volume and more recently amount and distribution of intra‐ and intermuscular adipose tissue. Also individual muscles can be assessed separately. However, with respect to muscle mass, the comparison of DXA with CT/MRI is rather difficult because DXA and QCT/MRI measure different physical parameters